Automated measurement of 25-OH Vitamin D on the LUMIPULSE®G1200: analytical verification and method comparison. Issue 3 (2nd July 2016) - Parra, Marina; Foj, Laura; Filella, Xavier
Abstract: Background: Because of its potential value in several pathologies, clinical interest in 25-hydroxy Vitamin D (25OH-D) is increasing. However, the standardisation of assays remains a significant problem. Our aim was to evaluate the performance of the novel Lumipulse G 25-OH Vitamin D assay (Fujirebio), comparing results with the Liaison (Diasorin) method. Methods: Analytical verification of the Lumipulse G 25-OH Vitamin D assay was performed. Both methods were compared using sera from 226 patients, including 111 patients with chronic renal failure (39 on haemodialysis) and 115 patients without renal failure. In addition, clinical concordance between assays was assessed. Results: For Lumipulse G 25-OH Vitamin D assay, the limit of detection was 0.3 ng/mL, and the limit of quantification was 2.5 ng/mL with a 9.7% of coefficient of variation. Intra-and inter-assay coefficients of variation were <2.3 and <1.8% (25.4–50.0 ng/mL), respectively. Dilution linearity was in the range of 4.5–144.5 ng/mL. Method comparison resulted in a mean difference of −6.5% (95% CI from −8.8 to −4.1) for all samples between Liaison and Lumipulse G . Clinical concordance assessed by Kappa Index was 0.66. Conclusions: Lumipulse G 25-OH Vitamin D showed a good clinical concordance with the Liaison assay, although overall results measured in Lumipulse were higher by an average of 6.5%.